The Intersection of Sustainable Entrepreneurship and Public Service: A Bibliometric Analysis - Suwandi, Imam; Muftiadi, R. Anang; Alexandri, Mohammad Benny; Purnomo, Margo (Universitas Padjadjaran, 2024)
In this study, we explore the intersection of sustainable entrepreneurship and public service using a bibliometric analysis of the Scopus database from 1985 to 2023.Our findings highlight a significant development in research productivity since 2015, reflecting a focus on sustainability and governance. United States and China dominate the research landscape, this is a research gap where this research can be done in other countries as new research. The study highlights the potential for sustainable entrepreneurship to enhance public service delivery through innovation, governance, and technology. It also outlines future research directions and policy recommendations to promote sustainable practices within public services. The novelty of this paper is that it explores an interdisciplinary approach, using tools such as VOSViewer and Biblioshiny, to map research trends and identify research gaps in the literature. This study can provide recommendations for future research and policy development aimed at improving public service delivery through sustainable entrepreneurship.